Organoids for the Study of Retinal Development and Developmental Abnormalities - Vielle, Anne; Park, Yuna K.; Secora, Conner; Vergara, M. Natalia (Frontiers in Cellular Neuroscience, 2021)
The cumulative knowledge of retina development has been instrumental in the generation of retinal organoid systems from pluripotent stem cells. And these three-dimensional organoid models, in turn, have provided unprecedented opportunities for retinal research and translational applications, including the ability to model disease in a human setting and apply these models to the development and validation of therapeutic drugs. In this review we examine how retinal organoids can also contribute to our understanding of retinal developmental mechanisms, how this knowledge can be applied to modeling developmental abnormalities, and highlight some of the avenues that remain to be explored.